Desprotección de los derechos de la victima por incumplimiento del principio de celeridad procesal en los tramites de violencia intrafamiliar. - CALDERÒN GUALAN, BERTHA MARIA (2010)
This research is a detailed study of the Law Against Violence to Women and the Family, with a detailed study of the basic principles that should govern procedural formalities of domestic violence to the principle of free, readily available, speed and booking. Especially in its Article 20 of the Act provides for the convening of the conciliation hearing, noting that in the summons, the judge the date and time for the hearing to be held within a period of not less than two business days, or more than eight, counting from the date of the summons and the hearing may be postponed not only at the express request of both parties and joint. This provision is not currently met because procedures are in reals, if the claim is lodged early, the marking of the date for the settlement hearing is scheduled for a date too long, extending to more than a month in some cases, the term to expect the victim of domestic assault to get some protection by the Commissioner for Women and Families. This research is funded through a methodology based on the internal regulations of the University National de Loja, detailed study has been carried into practice to meet with the approval of the thesis report, the results, presented in the interpretation and analysis implementation of surveys and interviews with its proper discussion, which is combined with the verification of the objectives, the contrast of the assumptions and legal criteria, doctrine and opinion that support the reform proposal, to expose the Conclusions and Recommendations Final Report of this thesis.